The performing art of therapy acting insights and techniques for clinicians - O'Connell, Mark (Routledge, 2019)
The Performing Art of Therapy explores the myriad ways in which acting techniques can enhance the craft of psychotherapy. The book shows how, by understanding therapy as a performing art, clinicians can supplement their theoretical approach with techniques that fine-tune the ways their bodies, voices, and imaginations engage with and influence their clients. Broken up into accessible chapters focused on specific attributes of performance, and including an appendix of step-by-step exercises for practitioners, this is an essential guidebook for therapists looking to integrate their theoretical training into who they are as individuals, find joy in their work, expand their empathy, increase self-care, and inspire clients to perform their own lives
Keywords: Psychotherapy; Client-centered psychotherapy; Psychotherapist and patient